1999
DOI: 10.1097/00007632-199911150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response to Submaximal Isometric Contractions of the Paravertebral Muscles

Abstract: At a threshold intramuscular pressure of 30-40 mm Hg during muscle contraction, oxygenation in the paravertebral muscles is significantly reduced. The effect of further increase in intramuscular pressure on tissue oxygenation over time may be compensated for by an increase in blood pressure and heart rate. Surface electromyogram amplitudes and intramuscular pressure can be used as indicators of paravertebral muscle force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
2

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 27 publications
6
60
2
Order By: Relevance
“…Jensen et al [20] found a significant decrease in the oxygenation of the paravertebral muscles with corresponding intramuscular pressure levels of between 30 mmHg and 40 mmHg. However, these results are only given for six out of nine subjects in the study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Jensen et al [20] found a significant decrease in the oxygenation of the paravertebral muscles with corresponding intramuscular pressure levels of between 30 mmHg and 40 mmHg. However, these results are only given for six out of nine subjects in the study.…”
Section: Discussionmentioning
confidence: 98%
“…According to the model, a muscle contraction leads to an increase in intramuscular pressure [20]. When the compartment pressure rises above a physiological threshold, the blood supply is reduced and the tissue's oxygen content decreases [11,28,44].…”
mentioning
confidence: 99%
“…The most likely reason for the discrepancy between the two studies is that RILL involves considerable isometric activity in the erector spinae muscles, whereas the muscle contractions during cycling are predominantly isotonic in nature. Previous research that has used NIRS to evaluate erector spinae hemodynamics during isometric exercise suggests that the decrease in BV is due to a reduced blood perfusion (occlusion) that is secondary to the increase in intramuscular pressure (Jensen et al 1999). McGill et al (2000 reported that erector spinae OXY decreased systematically during isometric contractions ranging from 2% to 30% maximum voluntary contraction (MVC), and suggested that this decrease was most likely due to a reduction in BV.…”
Section: Nirs Trends During Rillmentioning
confidence: 99%
“…Recently, several studies have used NIRS to examine localized changes in muscle oxygenation and blood volume during isometric contractions of the lower back (Jensen et al 1999;Kunimune et al 1999;McGill et al 2000;Yoshitake et al 2001). These studies suggest that NIRS is a sensitive technique for measuring tissue oxygenation and blood volume changes during such contractions, and therefore could be useful in the measurement of localized muscle fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies (Jensen et al 1999;McGill et al 2000;Yoshitake et al 2001) have used continuous wave NIRS to examine the trends in erector spinae OXY and BV during isometric contractions of the back. The evidence from these studies suggests that NIRS can be used to objectively evaluate low-back muscular endurance and fatigue.…”
Section: Introductionmentioning
confidence: 99%